The Mediated Effect of Job Satisfaction on the Influence of Organizational Climate and Transformational Leadership on the Performance of Permanent Employees at the Production Operator Level in the Automotive Industry - Hutabarat, Rinsan; Yusnita, Nancy; Sunaryo, Widodo (Riviera Publishing, 2025)
The automotive industry is a labor-intensive sector that relies on optimal employee performance, especially at the production operator level, to maintain efficiency, quality, and competitiveness. However, various challenges such as high work pressure, productivity demands, and organizational dynamics can affect employee work performance. This study aims to understand how job satisfaction mediates the impact of organizational climate and transformational leadership on the performance of permanent operator-level employees in the production department of the automotive industry. A quantitative approach was applied in this study, and data were obtained through surveys and literature review. To analyze the collected data, path analysis technique was used. The findings showed a positive and significant impact of organizational climate and transformational leadership on employee performance and job satisfaction. In addition, job satisfaction is also proven to have a significant influence on employee performance. Job satisfaction functions as a mediating variable, which means that the influence of these factors on performance is not only direct, but also indirect through increased job satisfaction. Thus, improving the organizational climate and the application of transformational leadership are critical to improving job satisfaction, which will ultimately lead to improved performance, particularly in the automotive production sector.